Stress and coping strategies among higher secondary and undergraduate students during COVID-19 pandemic in Nepal. - Durga Rijal; Kiran Paudel; Tara Ballav Adhikari; Ashok Bhurtyal (Public Library of Science (PLoS), 2023)
Coronavirus Disease (COVID-19) pandemic has profoundly affected lives around the globe and has caused a psychological impact among students by increasing stress and anxiety. This study evaluated the stress level, sources of stress of students of Nepal and their coping strategies during the pandemic. A cross-sectional web-based study was conducted during the complete lockdown in July 2020 among 615 college students. Stress owing to COVID-19 and the lockdown was assessed using the Perceived Stress Scale (PSS), and Brief Coping Orientation to Problems Experienced (Brief COPE) was used to evaluate coping strategies. To compare the stress level among participants chi-square test was used. The Student's t-test was used to compare Brief COPE scores among participants with different characteristics. The majority of study participants were female (53%). The mean PSS score was (±SD) of 20.2±5.5, with 77.2% experiencing moderate and 10.7% experiencing a high-stress level. Moderate to high levels of stress were more common among girls (92.6%) than boys (82.7%) (P = 0.001). However, there was a significant difference in perceived stress levels disaggregated by the students' age, fields and levels of study, living status (with or away from family), parent's occupation, and family income. The mean score for coping strategy was the highest for self-distraction (3.3±0.9), whereas it was the lowest for substance use (1.2±0.5). Students with a low level of stress had a higher preference for positive reframing and acceptance, whereas those with moderate to high levels of stress preferred venting. Overall, students experienced high stress during the lockdown imposed as part of governmental efforts to control COVID-19. Therefore, the findings of our study suggest stress management programs and life skills training. Also, further studies are necessary to conduct a longitudinal assessment to analyse the long-term impact of this situation on students' psychological states.